INTEGRATION OF TEACHER PRENEURSHIP, RELIGIOSITY, AND ENTERPRENEURIAL CULTURE INCREASING STUDENTS INTEREST ENTERPRENEURSHIP IN DIGITAL ERA - Mohamad Johan Saril; Edy Dwi Kurniati; Uswatun Chasanah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The rapid development of the digital era has created new opportunities and challenges in entrepreneurship education, requiring educational institutions to prepare students who are innovative, adaptive, and possess strong entrepreneurial values. In this context, teacherpreneurship, religiosity, and entrepreneurial culture are considered important factors in fostering students’ entrepreneurial interest. Therefore, this study aims to systematically examine the integration of teacherpreneurship, religiosity, and entrepreneurial culture in enhancing students’ entrepreneurial interest in the digital era. This study employed a Systematic Literature Review (SLR) method using the PRISMA protocol. The research stages included identification, screening, eligibility assessment, and inclusion of relevant studies. A total of 187 articles were retrieved from Google Scholar, Scopus, and DOAJ databases published between 2020 and 2025. After applying inclusion and exclusion criteria, 28 articles were selected and analyzed. The findings indicate that: (1) teacherpreneurship significantly enhances students’ motivation, creativity, and entrepreneurial competence; (2) religiosity, particularly Islamic values such as amanah (trustworthiness), ihsan (excellence), and diligence, positively shapes entrepreneurial character and intention; (3) entrepreneurial culture in schools creates a supportive ecosystem for entrepreneurial learning; and (4) the digital era strengthens these dimensions through digital literacy and technology-based entrepreneurial activities. In conclusion, the integration of teacherpreneurship, religiosity, and entrepreneurial culture plays a strategic role in increasing students’ entrepreneurial interest. These findings highlight the need for an entrepreneurship education model that combines teacherpreneur roles, religious values, and digital-based school culture to produce innovative, ethical, and competitive graduates. ABSTRAK Perkembangan pesat era digital telah menciptakan peluang dan tantangan baru dalam pendidikan kewirausahaan, sehingga lembaga pendidikan dituntut untuk mempersiapkan peserta didik yang inovatif, adaptif, dan memiliki nilai-nilai kewirausahaan yang kuat. Dalam konteks ini, teacherpreneurship, religiositas, dan budaya kewirausahaan dipandang sebagai faktor penting dalam menumbuhkan minat berwirausaha peserta didik. Oleh karena itu, penelitian ini bertujuan untuk mengkaji secara sistematis integrasi teacherpreneurship, religiositas, dan budaya kewirausahaan dalam meningkatkan minat berwirausaha peserta didik di era digital. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan protokol PRISMA. Tahapan penelitian meliputi identifikasi, penyaringan, penilaian kelayakan, dan inklusi studi yang relevan. Sebanyak 187 artikel diperoleh dari basis data Google Scholar, Scopus, dan DOAJ yang diterbitkan pada tahun 2020–2025. Setelah melalui proses seleksi berdasarkan kriteria inklusi dan eksklusi, sebanyak 28 artikel dipilih dan dianalisis. Hasil penelitian menunjukkan bahwa: (1) teacherpreneurship secara signifikan meningkatkan motivasi, kreativitas, dan kompetensi kewirausahaan peserta didik; (2) religiositas, khususnya nilai-nilai Islam seperti amanah, ihsan, dan kerja keras, berpengaruh positif dalam membentuk karakter dan niat berwirausaha; (3) budaya kewirausahaan di sekolah menciptakan ekosistem yang mendukung pembelajaran kewirausahaan; dan (4) era digital memperkuat ketiga dimensi tersebut melalui literasi digital dan aktivitas kewirausahaan berbasis teknologi. Simpulannya, integrasi teacherpreneurship, religiositas, dan budaya kewirausahaan memiliki peran strategis dalam meningkatkan minat berwirausaha peserta didik. Temuan ini menegaskan pentingnya pengembangan model pendidikan kewirausahaan yang mengintegrasikan peran teacherpreneur, nilai-nilai religius, dan budaya sekolah berbasis digital untuk menghasilkan lulusan yang inovatif, beretika, dan berdaya saing.